“Venha para o sindicato” ou “reze para chover”: o sindicalismo da agricultura familiar no período recente - análise da atuação da FETRAF-RS entre 2016 a 2022 - Lazzaretti, Mateus (2024)
This dissertation investigates how the family farming unionism, especially the Federation of Family Farming Workers of the state of Rio Grande do Sul (FETRAF-RS), organized its repertoire of interaction with the State from 2016 to 2022, which covers the rise of right-wing governments to the federal executive power and the resurgence of the orthodox neoliberal project. This is done through the adoption of a historical materialist theoretical-methodological framework, drawing on the contributions of Gramsci and Poulantzas to understand the State and civil society, as well as the notion of repertoires of action by Charles Tilly to analyze FETRAF-RS's engagement with the State. Aligned with this framework, qualitative methodological tools such as document analysis and semi-structured interviews are used for data collection, along with content analysis techniques for data treatment. The corpus of the work consists of: 13 interviews conducted with past and current union leaders of FETRAF and allies who held positions in the State; FETRAF documents, such as statutes, congressional resolutions, booklets, guidance circulars, informative materials, and historical records; and the disclosure of FETRAF-RS actions between 2016 and 2022 published on the Federation's Facebook profile. As results, it was identified that during the governments led by the PT (Workers' Party), social movements experienced new possibilities of interaction with the State, particularly through the strengthening of structures created in response to social struggles, such as the Ministry of Agrarian Development (MDA), which began to include union leaders and movement allies in its leadership and subsecretariats. During this period, a repertoire of interaction marked by annual and regular negotiation with the government and the implementation of public policies was established, absorbing the energies of FETRAF-RS leadership and subordinating other repertoires to this dynamic. The relationship with the base revolved around providing services and presenting the results of union action. However, this dynamic resulted in a certain dependence on FETRAF unionism, leading to a crisis of action when this interaction with the federal government was unilaterally interrupted with the rise of governments hostile to left-aligned social movements. The 2016 Coup and subsequent governments until 2022 restricted the access of subaltern classes to the State, with reduced resources, dismantling of public policies, and the extinction of the MDA. Nevertheless, FETRAF's action repertoire was diffuse, with predominant attempts at Dialogue and Negotiation with state and federal governments, albeit without effectiveness. Moments of Protest and Direct Action were less numerous and had lower base adherence, except for mobilizations against social security reform proposals, which were successful for family farming.